2002
DOI: 10.1093/geronb/57.4.s209
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in Living Arrangements Among Elders in Japan: Does Health Make a Difference?

Abstract: Poor health does trigger changes in living arrangement. Both physical (i.e., chronic conditions and functional status) and mental (i.e., depressed affect) health conditions play a role in such transitions. Because health conditions are correlated with competing risks of mortality, attrition, and proxy interview, health effects on changes in living arrangement are likely underestimated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
77
1

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(85 citation statements)
references
References 42 publications
7
77
1
Order By: Relevance
“…In Japanese culture, frail or widowed older people are commonly cared for by relatives (Kono, 1991). A national based data showed that 64% of elderly Japanese coresided with their children, and that functional impairment increased the likelihood of living with children (Brown et al, 2002). Japanese tradition expects women to take care for their elderly or disabled parents until their death, and 85% of those who care for elderly parents or relatives are women (Horlacher, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In Japanese culture, frail or widowed older people are commonly cared for by relatives (Kono, 1991). A national based data showed that 64% of elderly Japanese coresided with their children, and that functional impairment increased the likelihood of living with children (Brown et al, 2002). Japanese tradition expects women to take care for their elderly or disabled parents until their death, and 85% of those who care for elderly parents or relatives are women (Horlacher, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Elderly parents may prefer cohabitation with children to obtain physical, mental and economic support. Studies on the elderly in Japan and the US have found that increased parental needs for care are positively correlated with the probability of parent-child cohabitation (Johar et al, 2010;Brown et al, 2002;Dostie and Le´ger, 2005;Silverstein, 1995). The Javanese, the largest ethnic group in Indonesia, have been found to have preferences for family members to live close together (Beard and Kunharibowo, 2001).…”
Section: Reasons For Cohabitation and Related Literaturementioning
confidence: 99%
“…Some research on individual level transitions has examined populations in China, Japan and Taiwan (Brown et al, 2002;Gu & Zeng, 2004;Liang, Liu, & Gu, 2001;Tang, Jiang, & Futatsuka, 2002;Zimmer, Liu, Hermalin, & Chuang, 1998); however, examinations of population-wide functional status trends for Asia are in their relative infancy. Schoeni et al (2006) recently demonstrated declines in prevalence rates for several functional limitation and disability indicators for Japan similar to what has been seen in the United States, while and Zimmer, Martin, and Chang (2002) show less favorable trends occurring for Taiwan.…”
Section: Introductionmentioning
confidence: 99%